IDENTIFICATION OF FORMALDEHYDE IN UNBRANDED WET NOODLES AT TRADITIONAL MARKETS OF TAMBUN SELATAN USING TEST KIT METHODS AND UV-VIS SPECTROPHOTOMETRY (Jurnal Mitra Kesehatan, 2021)
Introduction: Wet noodles are flour-based foods that are widely consumed by the community because of their easy processing. The high water content in wet noodles makes the noodles not last long. In fact, there is still a preservative in wet noodles that is not used, namely formaldehyde. The purpose of this study was to determine whether there was formaldehyde in unbranded wet noodles in the Traditional Market of South Tambun District and to determine the level of formaldehyde in unbranded noodles in the Traditional Market of South Tambun District. Method: This research was conducted at the STIKes Mitra Keluarga laboratory. The type of research used is descriptive. There are 7 samples taken from 4 different markets. The sample was tested using a formaldehyde test kit and resulted in 6 positive formaldehyde samples. According to SNI, formaldehyde should not be in wet noodles. So that the results of the 6 samples did not meet the quality requirements of wet noodles. Results: Furthermore, the positive sample was determined using a UV-VIS spectrophotometer and Nash reagent. The lowest level of formaldehyde is 18.61 mg/L while the highest level is 738.45 mg/L. Conclusion: First, the regulation is not yet known by the producers because it is classified as traditional. Second, there is no good control from authorized institutions or officers. Third, the lack of guidance for producers